Students’ Motivation In Learning Physical Education Using The Game-Based Method - Wibawa, Dary; Wibawa, Brilliant Chandra; Lusianti, Septyaning; Ussya'en, Muhammad (Medical : Jurnal Kesehatan dan Kedokteran, 2025)
The background of this research problem is unmatched between the kinesthetic students characteristic and the reality on the field. Our observations many students are less interested participating in learning, because they feel boring, so our hypothesis is The gaming-method suspect effective because students with kinesthetic characteristics have physical skills that involve intelligence and cognitive as well as affective and attitudes. Therefore, interactive, holistic, integrative, scientific, contextual, thematic, effective, collaborative, and student-centered learning is needed, as well as the implementation of learning in the field that is directed using learning models/methods related to these characteristics. This study aims to determine is there a correlation or influence the modification of learning with the gaming-method in students motivation, so it can be used as an innovation in “PJOK” learning. This research method is Class Action Research (CAR) with an empirical model. Data were analyzed using the Likert Scale and  qualitative descriptive analysis carried out in 2 cycles with two meetings discussing the topic of student characteristics and the selection of appropriate learning methods. The participants of this research are student in class “9 C of SMPN 7 Kediri” were 32 students. Research shows that play method has an effective relationship and can increase student motivation in “PJOK” lessons in class “9 C of SMPN 7 Kediri”.